Sistem Pendukung Keputusan Prediksi Persediaan Barang Menggunakan Metode Double Exponential Smoothing (Studi Kasus : Toko Berjaya Selang) - Opi Sopiyah (CV. Multi Kreasi Media, 2024)
Decision support system is one of the information technologies used to assist decision making by utilizing available data and information. In this study, a decision support system was designed to predict inventory levels in heavy equipment spare part stores using the Double Exponential Smoothing (DES) method. The results of the study showed that the DES method can be used to predict inventory levels in heavy equipment spare part stores with high accuracy. In this study, it was found that the optimal alpha (α) and beta (β) values were 0.2 and 0.1, respectively. The predicted inventory level for the next period can be used to assist in decision making for inventory procurement in heavy equipment spare part stores. With this decision support system, it is expected to help the management of heavy equipment spare part stores optimize inventory and improve inventory procurement efficiency. As well as using several sistem support tools including the internet, web browser, XAMPP, MySQL and using the PHP programming languages.